Potential alcohol use disorder (AUD) among men who have sex with men (MSM) in Ireland. (20th October 2021) - Daly, FP; O'Donnell, K; Davoren, MP; Noone, C; Weatherburn, P; Quinlan, M; Foley, B; Igoe, D; Barrett, PM
Abstract: Background: Alcohol consumption is a major public health concern in Ireland. Alcohol use disorder (AUD) appears to disproportionately affect men who have sex with men (MSM). However, little is known about the prevalence of AUD in this group in Ireland specifically, and the characteristics of MSM who may struggle with this. Methods: The European MSM Internet Survey 2017 was an online, self-completed, anonymous questionnaire among MSM residing in Ireland. Standardised questions were used to explore a variety of topics. The validated CAGE-4 questionnaire was used to screen for potential AUD, defined as a CAGE-4 score of ≥ 2 out of 4. Multivariable-adjusted logistic regression analysis was used to identify factors associated with potential AUD. Results: In total, 1, 793 MSM met inclusion criteria, and 31% screened positive for AUD. We observed higher odds of possible AUD among MSM who were bisexual (vs. gay/homosexual) (aOR 1.48 95%CI 1.01-2.18), native to Ireland (vs. non-native) (aOR 1.49 95%CI 1.12-1.96), unemployed (vs. employed) (aOR 1.80 95%CI 1.02-3.16), had used illicit drugs in the previous year (vs. none) (cannabis only, aOR 1.74 95%CI 1.14-2.63) (other illicit drugs, aOR 2.28 95%CI 1.67-3.09), reported anxiety/depression (vs. none) (aOR 1.73 95%CI 1.12-2.66), and MSM who experienced homophobic abuse (vs. never) (aOR 1.55 95%CI 1.09-2.22). Student MSM were less likely to screen positive for AUD (vs. employed) (aOR 0.65 95%CI 0.46-0.93). Conclusions: The prevalence of AUD appears to be higher in the MSM population compared to the general male population in Ireland. Targeted interventions may be warranted to reduce the burden of AUD among MSM. Key messages: The prevalence of AUD appears to be higher in the MSM population compared to the general male population in Ireland. Targeted interventions may be warranted to reduce the burden of AUD among MSM.